Pengaruh Lama Penyangraian Manual Terhadap Karakteristik Kakao Bubuk - Sri Wijanarti; Annie Mufyda Rahmatika; Ratih Hardiyanti (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
Cacao powder is one of derivative products of cacao, applied in many industries such as chocolate drink, confectionary, bakery, etc cacao powder demand increased year by year. Cocoa powder aroma and taste are determined by cacao processing stages, especially roasting. Maillard reaction occurs during roasting, produces aroma and taste compounds. The purpose of this study was to evaluate the effect of roasting to cocoa powder characteristics. The study was conducted by roasting cocoa bean using manual equipment at 135oC in different time interval which were 5, 10, and 15 minutes. The results were compared to 40 minutes roasted cocoa bean using roaster at 135oC as control. Then the cocoa bean was further processed into cocoa powder. The cocoa powder was used to analyze the physicochemical and organoleptics characteristics. Optimum roasting time was obtained by 15 minutes roasting based on physichochemical and preference test.